Review of the Australian Apiocera minor Norris species-group (Diptera: Apioceridae) with a revised key to species - Yeates, David K.; Oberprieler, Stefanie K. (Zootaxa, 2013)
The Australian Apiocera minor species-group is reviewed. We provide a key to the species groups of Paramonov (1953) in Apiocera Westwood and all described species in the A. minor species group: A. mackerrasi Paramonov, A. cerata Par-amonov, A. australis Paramonov, A. newmani Norris, A. minor Norris, A. vespera Paramonov, A. macrocerata sp. n., A. evansi sp. n., A. rieki sp. n., A. collessi sp. n., A. mullewa sp. n. and A. microeremia sp. n. This brings the total number of species in the group to 12. Habitus, wing, abdomen and genitalic images and distribution maps are provided. All species in the A.minor group are diagnosed. Our studies have revealed a number of undescribed species in the ANIC that are rep-resented by few and/or poorly preserved specimens.